KAJIAN ELEMENTAL-KUANTITATIF TERHADAP KAPAK PERUNGU TIPE JANTUNG KOLEKSI BALAI ARKEOLOGI DENPASAR (BALI, NTT, NTB), MUSEUM BALI, DAN MUSEUM MANUSIA PURBA GILIMANUK - Ary Kesuma Puja, Gusti Ngurah (Humanis, 2016)
Bali Island is famous about lot of archaeological evidence who found in this area. Archaeological evidence who counted many found at this area is bronze artifacts. Some of bronze artifacts able to found only at Bali Island area, one of them is axe of heart-blade type. The fact is to be one of many reason to choice axe of heart- blade type as research problem. This research purpose is to know about material producting and made technique form axe of heart-blade type base from analysis result may from persentace at every metal elements who contained in bronze metal. Analysis result of this research show that obtain two metal elements with persentace commulatif more than 1% including copper and tin at every sample. Base from the fact, material producting composition know obtain of three sample was by two primary material producting or usually call binary alloy. Base of persentace commulatif from every primary elements and secundary elements there are at three sample , approximately the technique used to made three sample axe of heart-blade type is metal casting technique.
Keywords: Bali Island, axe of heart-blade type, material producting, technique